Factors associated with pregnancy uptake decisions among seropositive HIV people receiving antiretroviral therapy in sub‐Saharan Africa: A systematic review - Abdul Razak Doat; Roberta Mensima Amoah; Kennedy Diema Konlan; Kennedy Dodam Konlan; Juliana Asibi Abdulai; Margaret W. Kukeba; Iddrisu Mohammed; Joel Afram Saah (Wiley, 2022)
Abstract Aim This study determined the factors associated with pregnancy uptake decision among seropositive HIV people receiving antiretroviral therapy in sub‐Saharan Africa. Design Systematic review. Methods The population, intervention, comparison and outcomes framework was adopted to search for literature after a scoping review using the preferred reporting items for systematic reviews and meta‐analyses guidelines adopted in searching, and screening articles from four databases (PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, and Google scholar) to find 12 articles suitable for this study. Results Motivators of pregnancy uptake among HIV‐positive women include desire to have children, knowledge about PMTCT, cultural duty for married women to have children, and household income. Demotivating factors included the modern method of contraception and burden associated with pregnancy. Conclusion There is a need to improve on services that reduce conception‐related risks especially for women who choose to conceive and to incorporate fertility‐related counselling into HIV treatment services.